Effect of Sorbitol on the Pharmacokinetic Profile of Lamivudine Oral Solution in Adults: An Open‐Label, Randomized Study. Issue 3 (11th December 2017) - Adkison, Kimberly; Wolstenholme, Allen; Lou, Yu; Zhang, Zhiping; Eld, Amy; Perger, Teodora; Vangerow, Harald; Hayward, Katy; Shaefer, Mark; McCoig, Cynthia
Abstract : In children aged ≤4 years, the relative bioavailability of lamivudine oral solution was 37% lower than that of a tablet formulation. An open‐label, four‐way crossover study was conducted in healthy adults to evaluate the effect of sorbitol, a common liquid excipient, on the pharmacokinetics of lamivudine oral solution (ClinicalTrials.gov identifier, NCT02634073). Sixteen subjects were randomized to one of four sequences consisting of four doses of lamivudine 300 mg (10 mg/mL) alone or with sorbitol 3.2, 10.2, or 13.4 g. Sorbitol 3.2, 10.2, and 13.4 g decreased lamivudine maximum concentration ( C max ) by 28%, 52%, and 55% and area under the concentration–time curve from time 0 to 24 h (AUC0‐24 ) by 20%, 39%, and 44%, respectively. Three subjects (19%) reported five nonserious adverse events (one drug‐related). The dose‐dependent effects of sorbitol on lamivudine C max and AUC0‐24 reveal an absorption‐based interaction that may decrease lamivudine exposure in patients coadministered sorbitol‐containing medicines.